Green IT/IS assessment tool for enterprises - Mazlina, Abdul Majid; Anthony, Bokolo Jnr.; Awanis, Romli; Syahnizam, Abdullah Sani (2018)
GiTaT is an autonomous based tool that supports the assessment of enterprise towards inclusion of sustainability considerations to enhance enterprise environmental performance for ecological protection towards sustainable development.